PERKEMBANGAN ORGANISASI PEMUDA PANCASILA DI BANDA ACEH TAHUN 1984-2016 - Syahrul Indra; Teuku Abdullah; Zainal Abidin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2017)
ABSTRACTIn accordance with the above title, which is "Development of Pancasila Youth Organization in Banda Aceh In the Year 1984-2016",the purpose of this study was (1) To find out how the background of the establishment of Pancasila Youth Organization in Banda Aceh in 1984-2016. (2) To explain how the development of the Pancasila Youth Organization in Banda Aceh in 1984-2016. (3) To describe the influence of Pancasila Youth Organization in Banda Aceh in 1984-2016. This study used a qualitative approach and methods used is the historical method. Pengumpula n data is done by observation, documentation, and interviews. Based on the research results obtained information that (1) History of Pancasila Youth Organization in Banda Aceh was founded in 1984 by Murshamina and colleagues with the aim to break the communist movement in the city of Banda Aceh. (2) The development of the Pancasila Youth Organization of the Year 1984-1999 is the future Pancasila Youth Organization in Banda Aceh bestatus led Organizations (OKP) for the years 1999 to 2016 was the transformation of the Youth Organization Pancasiladi Banda Aceh to Community Organisations (CBOs), Years 2003-2006 Condition is experiencing Vacuum Pancasila Youth Organization, 2006-2016 Year period is Pancasila Youth Organization in Banda Aceh experienced the Resurrection, and Perioderisasi Management of Pancasila Youth Organization in Banda Aceh of the Year 1984-2016, Gait Pancasila Youth Organization in Banda Aceh, Gait Kader Pancasila Youth Organization in Banda Aceh, Pancasila Youth Organization cadre system in Banda Aceh, as well as lines of Pancasila Youth Organization Coordinating Centre until Commissariat. (3) Effect of Pancasila Youth Organizations in the political field is productive cadre organization serves as a public office even as legislative members at the DPRK and the provincial parliament. Influence in the social sphere is ketelibatan this organization in the community problems, such as volunteering as tsunamis, fires, floods, and, make a public discussion, and share food in the streets when the fasting month for the community. Influence in the field of education is that many of its members became academic at Syiah Kuala University and the State Islamic University of Ar-Raniry, Darussalam, Banda Aceh. Keywords: The development, organization, Pemuda Pancasila.ABSTRAKSesuai dengan judul di atas, yaitu “Perkembangan Organisasi Pemuda Pancasila di Kota Banda Aceh Pada Tahun 1984-2016”, maka tujuan penelitian ini ialah (1) Untuk mengetahui bagaimana latar belakang berdirinya Organisasi Pemuda Pancasila di Kota Banda Aceh tahun 1984-2016. (2) Untuk menjelaskan bagaimana perkembangan Organisasi Pemuda Pancasila di Kota Banda Aceh tahun 1984-2016. (3) Untuk mendeskripsikan pengaruh  Pemuda Pancasila di Kota Banda Aceh tahun 1984-2016. Penelitian ini mengunakan pendekatan kualitatif dan metode yang digunakan adalah metode sejarah.Pengumpulan data dilakukan dengan teknik observasi, dokumentasi, serta wawancara. Berdasarkan hasil penelitian diperoleh informasi bahwa (1) Sejarah Organisasi Pemuda Pancasila di Kota Banda Aceh didirikan tahun 1984 oleh Murshamina dan kawan-kawan dengan tujuan untuk mematahkan gerakan komunis di Kota Banda Aceh. (2) Perkembangan Organisasi Pemuda Pancasila Tahun 1984-1999 ialah masa Organisasi Pemuda Pancasila di Kota Banda Aceh bestatus Organisasi Kepemudaan (OKP), tahun 1999-2016 ialah transformasi Organisasi Pemuda Pancasiladi Kota Banda Aceh ke Organisasi Kemasyarakatan (Ormas), Tahun 2003-2006 ialah Kondisi Organisasi Pemuda Pancasila Mengalami Kevakuman, Tahun 2006-2016 ialah masa Organisasi Pemuda Pancasila di Kota Banda Aceh mengalami Kebangkitan, serta Perioderisasi Kepengurusan Organisasi Pemuda Pancasila di Kota Banda Aceh dari Tahun 1984-2016, Kiprah Organisasi Pemuda Pancasila di Kota Banda Aceh, Kiprah Kader Organisasi Pemuda Pancasila di Kota Banda Aceh, Sistem Pengkaderan Organisasi Pemuda Pancasila di Kota Banda Aceh, serta Garis Koordinasi Organisasi Pemuda Pancasila dari Pusat hingga Komisariat. (3) Pengaruh dari Organisasi Pemuda Pancasila di bidang politik ialah produktifnya kader organisasi ini menjabat sebagai jabatan publik bahkan menjadi anggota legislatif di tingkat DPRK maupun DPRA. Pengaruh di bidang sosial ialah ketelibatan organisasi ini dalam permasalahan masyarakat, seperti menjadi relawan ketika tsunami, kebakaran, kebanjiran, dan, membuat diskusi-diskusi publik, serta membagi makanan di jalanan ketika bulan puasa untuk masyarakat.Pengaruh di bidang pendidikan ialah banyak anggotanya menjadi akademisi di Universitas Syiah Kuala dan Universitas Islam Negeri Ar-Raniry, Darussalam, Banda Aceh.Kata kunci: Perkembangan, Organisasi, Pemuda Pancasila.